Formulasi Mikroemulsi Ekstrak Terpurifikasi Daun Bayam Merah (Amaranthus tricolor L.) Sebagai Suplemen Antioksidan: Microemulsion Formulations of Purified Extract of Red Leaves Spinach (Amaranthus tricolor L.) as Antioxidant Supplements - Dwi Lestari Handayani; Yusriadi Yusriadi; Ririen Hardani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
A research has conducted about the microemulsion formulation of purified extract of red spinach leaves (Amaranthus tricolor L.) as an antioxidant supplement with the aim to be able to know the formula to form a microemulsion which meet the physical quality stability and determine antioxidant activity (IC50) of the preparation. Extracts prepared by maceration method using ethanol 96% and then later do the purification using solvent n-hexane and ethyl acetate, after it tested its antioxidant activity. Formula to form a microemulsion purified extract of red spinach leaves clear is to use virgin coconut oil (VCO) by 15%, tween 80 for 40%, 35% glycerin and 10% distilled water. Physical stability test was conducted on the organoleptic test, measuring the diameter of globules, pH test, test and test viscosity centrifugation. Test of antioxidant activity in vitro using DPPH method and using Vitamin C as a positive control. Measurement data were statistically analyzed using paired samples T test. The test results of antioxidant activity microemulsion purified extracts of spinach leaves, red show IC50 values on day 1 was 1.83 ppm and the 28th day amounted to 3.71 ppm. While vitamin C microemulsion shows IC50 values on day 1 of 0.24 ppm and the 28th day of 2.51 ppm. Despite the decreased antioxidant activity, but each of the stocks included in the category of very powerful antioxidants.